PENAFSIRAN KONSTITUSI TENTANG PENDIDIKAN PESANTREN PADA SATU SISTEM PENDIDIKAN NASIONAL - Marlinawati, Reni (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2012)
This paper is interpreting the provision of Article 31 paragraph (2), ‘the governmentshall establish and conduct a national education system’. Method of interpreting Article 31paragraph (2) is by using the method of socio-historical interpretation. This method is very suitable to the method used in excavating Pancasila by the President Soekarno. The main system in the national education system should be an Islamic education system (Pesantren) and not educational system which brought by colonizers. For a system that brought by the colonizers are not intended for the people of Indonesia, but for the colonizers. Therefore, the founding fathers passed a mandate ofArticle 31 paragraphs (2) that the government shall establish and conduct a national education system which is not discriminatory.